2022
DOI: 10.3390/biology11121717
|View full text |Cite
|
Sign up to set email alerts
|

Plant Flavonoids on Oxidative Stress-Mediated Kidney Inflammation

Abstract: The kidney is susceptible to reactive oxygen species-mediated cellular injury resulting in glomerulosclerosis, tubulointerstitial fibrosis, tubular cell apoptosis, and senescence, leading to renal failure, and is a significant cause of death worldwide. Oxidative stress-mediated inflammation is a key player in the pathophysiology of various renal injuries and diseases. Recently, flavonoids’ role in alleviating kidney diseases has been reported with an inverse correlation between dietary flavonoids and kidney in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
17
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 129 publications
3
17
0
Order By: Relevance
“…This is in line with how ISL is known to increase antioxidant effects. These results are in line with other research that has focused on how oxidative stress plays a part in the development of gentamicin-induced nephrotoxicity and how antioxidant therapy can help reduce its effects [18,19].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…This is in line with how ISL is known to increase antioxidant effects. These results are in line with other research that has focused on how oxidative stress plays a part in the development of gentamicin-induced nephrotoxicity and how antioxidant therapy can help reduce its effects [18,19].…”
Section: Discussionsupporting
confidence: 91%
“…We found that the antioxidant effects were also nephroprotective when we examined oxidative stress markers (MDA, NO, and GSH) in kidney tissue [18]. Following the treatment, there was a big drop in MDA and NO levels and a rise in GSH levels.…”
Section: Discussionmentioning
confidence: 88%
“…It is known that preeclamptic pregnancies are characterized by the presence of oxidative stress [26], an important process also reported in many other pathologies, including cancer [34,35]. Moreover, it has been reported that oxidative stress plays a key role in promoting the inflammation process [36,37]. Interestingly, we found that inducing oxidative stress in vitro significantly increased HTRA1 expression in both BeWo and HTR8/SVneo cell lines.…”
Section: Discussionsupporting
confidence: 61%
“…Bax stands as a pro-apoptotic protein, on the contrary, Bcl2 exerts anti-apoptotic effects. So, the tissue Bax/Bcl2 ratio is commonly used to predict especially the severity of oxidative stress-related mitochondrial damage (18).…”
Section: Discussionmentioning
confidence: 99%